2019
DOI: 10.1007/s42804-019-00029-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Morgagni hernia repair in children: systematic review

Abstract: Aim This study performed a systematic review on procedures, instruments, techniques, and outcomes of laparoscopy in children with Morgagni hernias (MH). Methods The literature was reviewed for articles online on PubMed with search terms "laparoscopy", "Morgagni", "hernia", and "children". The inclusion criteria included articles only in English, and in the pediatric age group of 0-18. Articles that did not meet the inclusion criteria were excluded. Results The literature search from 1997 to 2019 revealed 32 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
0
2
Order By: Relevance
“…The recurrence rate in open surgery has been reported as 42 to 50%. 13 14 15 In our study, the recurrence rate in the CS group was found to be lower than in the literature, with a rate of 10.5%.…”
Section: Discussioncontrasting
confidence: 80%
“…The recurrence rate in open surgery has been reported as 42 to 50%. 13 14 15 In our study, the recurrence rate in the CS group was found to be lower than in the literature, with a rate of 10.5%.…”
Section: Discussioncontrasting
confidence: 80%
“…There was no statistically significant difference between the two groups in terms of postoperative complications (p=027). While the recurrence rate in open surgical repair of MH has been reported as 42 to 50%, this rate has been reported between 0 to 42% in laparoscopic repairs in the literature [2,13,14]. In our study, recurrence was reported after surgery in one patient in each group, and no statistically significant difference was found between the two groups (p=0.612).…”
Section: Discussioncontrasting
confidence: 58%